From Sanad to Algorithms: The Transformation of Islamic Authority and the Reconstruction of Nusantara Islamic Epistemology in the Digital Age - Ahmad Ihsan Syarifuddin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article analyzes the transformation of Islamic religious authority in the digital era by examining the shift from a sanad-based epistemological structure to legitimacy mediated by digital platform algorithms. In classical Islamic scholarship, sanad functions as a mechanism of transmission, verification, and legitimation that ensures the continuity of religious knowledge and scholarly authority. However, the rise of digital media has reshaped the production and circulation of religious knowledge, where visibility, user engagement, and algorithmic recommendation systems increasingly determine who gains influence within the contemporary religious public sphere. This study aims to explain how these transformations affect the construction of religious authority and how Islamic epistemological traditions negotiate with emerging digital technological structures, this research employs a qualitative approach using a literature-based method that engages recent scholarship on religious authority, digital religion studies, and theories of the mediatization of religion. The analysis is conducted through a conceptual-critical framework that integrates Islamic epistemology with contemporary media theory. The findings suggest that the ongoing transformation should not be understood as a complete replacement of sanad-based authority by algorithmic systems. Rather, it reflects a process of hybridization between normative-transmissive legitimacy and performative-distributive legitimacy. The article proposes the concept of algorithmic authority as an analytical framework to understand how contemporary religious legitimacy is increasingly shaped through the interaction between traditional chains of scholarly transmission and the infrastructural logic of digital platforms. The main contribution of this study lies in developing a conceptual bridge between classical Islamic epistemology and the dynamics of authority in the digital public sphere, offering a new perspective for the study of digital Islam in contemporary Muslim societies.